Controle Fuzzy aplicado à otimização de um sistema eólico de velocidade variável - Sena, Francisco das Chagas Barbosa de (2015)
The development of a mathematical model for a system of wind power generation is complex, can be strongly affected by the wind variation and it s a non-linear problem. Due to these characteristics the analysis can be performed using a control system based on fuzzy logic, which improves a better adjust of the system to be controlled. In this paper, the performance of a variable-speed wind turbine controlled by a classic proportional controller (CPC), and a fuzzy logic controller (FLC) to adjust the angle of inclination of the blades is analyzed. In this case, it s possible to verify the effectiveness of the application of fuzzy logic, the ability to avoid fluctuations and improvement of the quality of electric power output, regardless of the original features of the proportional control applied. The CPC and the FLC were implemented using the Fuzzy Logic ToolboxTM and SIMULINK® software packages available in MATLAB®. The results show that the application of fuzzy logic to adjust the parameters of a controller can improve the dynamic performance of the wind turbine with respect to reducing the onset of fatigue loads, weather fluctuations and stabilization of electric power output